Excess liquidity and bank lending risks in the euro area - Zsolt Darvas; David Pichler (Bruegel, 2018)
Excess liquidity (defined as all kinds of commercial bank deposits held by the Eurosystem minus the minimum reserve requirements) in the euro area exceeded exteuro1,900 billion, or 17 percent of euro-area GDP, in September 2018. Holding such excess liquidity is costly for commercial banks, given that the currently negative (-0.4 percent) deposit facility interest rate applies on excess liquidity holdings. The current stock of excess liquidity implies an annual exteuro7.6 billion cost in total for those banks that hold this liquidity. More generally, the European Central Bank's negative deposit interest rate and asset purchases further reduced market interest rates, with a negative impact on banks' net interest income and thus profitability. This could incentivise a reach-for-yield race among banks. Additionally, the access to liquidity eased significantly and removed the liquidity constraint for most banks' lending activities. These factors might incentivise banks to engage in risky lending in order to improve their profits. This in turn might create financial stability risks. We clarify the definition of excess liquidity, to highlight the reasons why such a large amount of it is being held, and to assess its financial stability implications.
Keywords: 330